Using an eLearning Module to Facilitate Sepsis Knowledge Acquisition Across Multiple Institutions and Learner Disciplines. Issue 12 (December 2021) - Woods, Jason M.; Scott, Halden F.; Mullan, Paul C.; Badolato, Gia; Sestokas, Jeff; Sarnacki, Rachel; Wolff, Margaret; Lane, Roni; Dawson, Emily; Kaplan, Ron; Zaveri, Pavan
Abstract : Objective: Guidelines exist for care of pediatric sepsis, but no study has assessed the benefit of electronic learning (eLearning) in this topic area. The objective of this multicenter study was to assess knowledge acquisition and retention for pediatric sepsis across multiple health care provider roles, using an adaptive and interactive eLearning module. Methods: The study used pretest, posttest, and 90-day delayed test scores to evaluate provider knowledge after an adaptive and interactive eLearning module intervention. The eLearning module contained conditional logic-based assessments that allowed real-time adjustments of the displayed content according to each participant's demonstrated knowledge. Physicians, nurses, and advanced practice providers, primarily emergency department based, at 9 pediatric institutions were included. Changes in test scores were stratified by provider role. Results: A total of 574 participants completed the posttest, and 296 (51.6%) of those completed the delayed test. Across all providers, there was an increase in test scores of 15.7% between the pretest and posttest ( P < 0.001) with a large effect size as measured by Cramer's V. Across all providers, there was an overall test score increase of 5.2% ( P < 0.001) between the pretest and delayed test, with a small effect size. Conclusions: An eLearning module improved immediate and delayed pediatric sepsis knowledge in pediatric health care providers across multiple institutions and provider roles. Immediate knowledge gain was meaningful as indicated by effect sizes, although by the time of the delayed test, the effect was smaller. This module fills an important gap in currently available pediatric sepsis education.